Relationship between alcohol consumption and adverse childhood experiences in college students–A cross-sectional study - Šulejová, Karolína; Líška, Dávid; Liptáková, Erika; Szántová, Mária; Patarák, Michal; Koller, Tomáš; Batalik, Ladislav; Makara, Michael; Skladaný, Ľubomír (Frontiers in Psychology, 2022)
Abstract Background: Alcohol consumption is an important issue. Adverse childhood experiences (ACEs) can affect alcohol consumption later in life. Therefore, the main objective of this study was to test the association between ACE and the alcohol consumption in college students. Materials and methods: A cross-sectional study on college students was conducted during December 2021 and January 2022, Through the school web system, students received a standard questionnaire on alcohol consumption (AUDIT) and ACEs. The study involved 4,044 participants from three universities in Slovakia. Result: Compared to men, the incidence of emotional abuse by a parent, physical abuse by a parent, and sexual abuse was significantly higher in women (p < 0.001). Furthermore, women reported greater emotional and physical neglect (p < 0.001). The incidence of a high or very high AUDIT score in college students with ACE-0, ACE-1, ACE-2, ACE-3, and ACE-4+ was 3.8%, 4.7%, 4.1%, 6.4%, and 9.3%, respectively. Conclusion: More adverse childhood experiences were associated with increased alcohol consumption in both male and female university students. Baseline drinking was higher in male students, but increased drinking in relation to an increase in ACEs was higher in female students. These results point to gender-specific driving forces and targets for intervention. Keywords: adverse childhood experience, alcohol consumption